The Influence of Self-Efficacy and Peer Support on Resilience in Completing a Thesis - Farosi Illiyun Jauharah; Moesarofah Moesarofah (Universitas PGRI SUMATERA BARAT, 2025)
In completing their final assignments, students often face various challenges that can affect their level of resilience, while resilience is an important factor in determining academic success. This study aims to analyze the role of self-efficacy and peer support on students' resilience in writing their theses. The research design was a survey. The respondents were students of the Faculty of Education and Teacher Training, Universitas PGRI Adi Buana Surabaya, Class of 2021, who were writing their theses (N=131). Data collection used a valid and reliable measurement scale for self-efficacy, peer support, and academic resilience. Data analysis used multiple regression tests to test the hypothesis regarding the effect of self-efficacy and peer support on resilience in writing a thesis. The results showed that self-efficacy had a positive and significant effect on resilience in writing a thesis. The novelty of the study lies in the combination of self-efficacy and peer support variables, as well as the focus on the context of writing a thesis. The implications of the study provide a comprehensive understanding of the factors that influence student resilience in completing a thesis, to develop more effective support programs. While the limitations that need to be considered are related to the generalization of the research results to a wider population.Keywords: self-efficacy, peer support, resilience in writing a thesis, survey research